Effect of an Informative Pamphlet in Improving Parental Knowledge about Retinopathy of Prematurity (Medico Legal Update, 2020)
Introduction: The childhood blindness due to retinopathy of prematurity (ROP) can be prevented if infantsat risk are screened before the progression of the condition. The parental awareness on need of follow-upsfor screening and identification of ROP will help in reducing the incidence of childhood blindness due toROP.Method: In the present study an informative pamphlet was developed and distributed to find its effectivenessin improving the parents’ knowledge on retinopathy of prematurity. Quantitative research approach was usedwith pre-experimental pre-test post-test one group design. Conceptual framework used was General systemtheory by Ludwig Von Bertalanffy. Using convenience sampling method 30 parents of preterm babies wereselected. The baseline proforma and knowledge questionnaire were administered and later an informativepamphlet about ROP were given. Post-test knowledge assessment was done 7 days after the exposure topamphlet.Result and Discussion: The study finding showed an increase in the knowledge of parents on ROP after theexposure to pamphlet (Z=4.628, p=.001). An association was found between pre-test knowledge and previousparental knowledge on eye diseases in newborn babies (U=59, p=.048). The present study concludes that thepamphlet made by the researcher on ROP was effective in improving the parents’ knowledge about ROP.